Deprescribing Falls Risk Increasing Drugs in Older Adults - Kalim, Reham Ahmed (Trinity College Dublin. School of Pharmacy & Pharma. Sciences. Discipline of Pharmacy, 2023)
Aim: The purpose of this thesis was to examine the facilitators of, and barriers to, implementing deprescribing of falls risk increasing medicines (FRIDs) in healthcare professionals' practices, by exploring the perspectives of multiple stakeholders and integrating them with the existing literature, with a view to future use of this knowledge to inform an intervention that could readily be integrated into clinical practice without the need for significant additional resources. Methods: Two systematic reviews of the existing literature were undertaken. The first review investigated the role of pharmacists in medication management for older patients at hospital discharge. Scientific databases and the grey literature were searched systematically for randomised controlled studies addressing this topic. The Cochrane Handbook for Systematic Reviews of Interventions guided the data analysis and reporting. The second was a systematic review of qualitative studies that investigated patients' or carers' opinions of deprescribing FRIDs. The data from these studies were coded to the Theoretical Domains Framework (TDF) and the studies' quality was assessed using the Critical Appraisal Skills Programme (CASP) checklists. Semi-structured interviews were conducted with hospital doctors, general practitioners and pharmacists in Ireland. The data gathered during the interviews were transcribed verbatim. Initial deductive analysis mapped the themes identified to the domains of the TDF, followed by inductive analysis to generate additional themes and subthemes. NVivo 12 software (QSR International Limited, UK) facilitated the process of analysis. A focus group was also conducted with older adults to explore the results of previous research from their points of view, and to determine their ideas about how older people feel about FRIDs deprescribing to reduce the risk of falls. All qualitative data were matched with behavioural change techniques to suggest possible interventions for implementing deprescribing in primary and secondary care. Results: The first systematic review identified common interventions undertaken by pharmacists and their outcomes in hospital settings. Only mortality and healthcare use outcomes were eligible for meta-analysis. The rest of the outcomes were described and the results highlighted how pharmacists can preserve or enhance the quality of care for older adults with polypharmacy. The stakeholders' qualitative interviews and systematic data syntheses resulted in a rich account of themes and potential target behaviours. The main themes arising from data analysis included: environmental challenges (in hospitals and general practice clinics), patients' and family members' involvement, pharmacists' role in deprescribing, personal knowledge, concerns and reinforcement. Challenges and enablers were identified for each theme, supported by sample quotes. Commonalities across all stakeholder groups were identified. The data from all the above contributed to the design of a potential future intervention involving encouragement of patients to engage with their prescribers on the issues of deprescribing FRIDs, and concise education and reminder tools for healthcare professionals to facilitate more widespread consideration of deprescribing. Conclusion: In this thesis the beliefs, concerns and potential roles of core stakeholders in the deprescribing of FRIDs were investigated and analysed. The resultant data lays the foundation for implementation of future deprescribing interventions in clinical practice.
APPROVED
Keywords: deprescribing; older adult; falls; theoretical domains framework; fall-risk-increasing drugs